Trainees’ Perceptions towards the Practice of Competency Based Assessment for Learning in Oromia Colleges: In Particular to Shambu, Nakamte and D/Dollo CTE - Alemayehu Dheressa, Moti; Olana, Tamiru; Bekele, Ebisa (JOLLT Journal of Languages and Language Teaching, 2022)
This study investigated Trainees’ perceptions towards the practice of competency based assessment for learning in Shambu,Nakamte and D/Dollo College of Teachers Education in Oromia Region to realize their perceptions. Therefore, descriptive design was used. A close-ended and open-ended questionnaire items with five point Likert scale was administered to thirty two trainers. In addition, to substantiate the data obtained through questionnaires, interviews with 4 experienced instructors were also held. The quantitative data was analyzed to determine the status of instructors’ perception towards the practice of CBAFL. The qualitative data which was collected using interview was described qualitatively using narrative analysis. Results of the study revealed that instructors’ have unfavorable perception towards the practice of AFL. They perceived that the practice of CBAFL in the faculty was more of theoretical and most of them assumed that students need further practical training to perform to the standard in the actual job situations. Regarding the factors that affect the practice of assessment, almost all the participants believe the following are main factors: A heavy influence of the earlier approach to methods of teaching and assessment (behaviorist) which is usually practiced by instructors; instructors give more attention to grading instead of enabling trainees to be competent through careful engagement of practical assessment tools; in addition the participants of the study also enlisted the following as main factors: trainees are not responsible for their own learning; they give priority to passing exams rather than developing competence; lack of clarity on competence-based assessment among trainee and instructors. Large numbers of respondents held the view that the practice of CBAFL was not in line with future job requirements of the graduates.